Psycholinguistic Features Of Slang Vocabulary In The National Language (Eurasian Scientific Herald, 2022)
Currently, it is important to study from a scientific point of view the features of speech, language, which are considered means of communication. This article discusses the jargons used in the daily communication process. Slang words used by the younger generation, which is the main stratum of society, and explains the importance and necessity of learning slang vocabulary. The peculiar psycholinguistic features of slang words were scientifically analyzed.